Nanoscale Technologies in Highly Sensitive Diagnosis of Cardiovascular Diseases - Shi, Chaohong; Xie, Haotian; Ma, Yifan; Yang, Zhaogang; Zhang, Jingjing (Frontiers in Bioengineering and Biotechnology, 2020)
Cardiovascular diseases (CVD) remain the leading cause of death and morbidity in the world and are still the major contributor to healthcare costs. Although enormous progress has been made for CVD in diagnosis, there is an urgent need for more efficient early detection of CVDs, which forces the development of novel diagnostic tools. Currently, CVD diagnosis primarily relies on clinical symptoms based on molecular imaging (MOI), or biomarkers that are associated with CVDs due to involvement of multiple functions. However, sensitivity, specificity, and accuracy of the assays are still challenging for early-stage CVDs. Nano-material platform, due to its unique physicochemical properties, has been widely exploited and is identified as a promising candidate for improving the practical usage of the assay. In this review article, we present nanotechnology applications on CVDs diagnosis, introduce frequently used non-invasive cardiac immunoassay and imaging techniques, and summarize current achievements on CVDs diagnosis attributed to nanotechnologies.